Township home-based enterprises: the case of Pimville - Hadebe, Thamsanqa (My University, 2010)
Many informal sector scholars discovered that small informal businesses do not grow and develop. However scholars who went further and investigated factors influencing growth of these businesses did not cover all possible hindrances to growth. There are minor investigations with regards to South African township home-based enterprises, and there is also less information on the way in which growth of these businesses is affected by the location of a business or entrepreneur‟s social context. The purpose of this research is to investigate the following gaps concerning the hindrances to growth of township home-based enterprises: the way in which these businesses are affected by their social context, their nature and the way they access land. It focuses only on South African township home-based enterprises. The factors that are investigated includes: factors that arise due to the nature of the businesses (being informal and operating at small scale), the factors that arise due to the businesses‟ social context and factors that arise due to the stigma attached to the informal sector businesses. Pimville was used as the case study for this research and the interviews conducted a census rather than sample. A Questionnaire was used as the tool for data collection but data collection was in the form of interviews. Interviews were in the interviewee‟s language of choice and translated to English by interviewers. A team of eleven interviewers was used and most of them could at least understand most spoken languages in the area. The findings of this research indicate that, factors that influence growth of township home-based enterprises are: growth objective, employee recruitment and development, product market, financial resources, local business collaboration or networking, owner‟s motivation, owner‟s education background and training qualification, past business experience, size of the founding team, environment/industry specific factors, characteristics of the firm or business and entrepreneur-community relationships. Although these factors either have a negative or positive influence on growth, negative influences overcome positive influences. However, some of the factors that have negative influence have a combine influence that create other factors. Therefore interventions should focus on addressing key factore and this will result in the trickle down to other negative factors. Page | vi TABLE OF CONTENTS Declaration--------------------------------------------------------------------------------------------------